THE INFLUENCE OF FAMILY SUPPORT AND MATERNAL READINESS ON PREGNANT WOMEN'S ANXIETY IN THE THIRD TRIMESTER BEFORE CHILDBIRTH AT TPMB TELUK JAMBE BARAT, KARAWANG REGENCY - Rahmadyanti, Rahmadyanti; Andriani, Lena Kuswati (HEARTY, 2025)
Background: Family support, especially support obtained from the husband, will create inner peace and feelings of happiness in the wife. The quality and quantity of family support is assessed from three parameters, namely, material, informational and psychological support. So family support has a big influence on the mother's emotional atmosphere in reducing the mother's anxiety in preparation for the birthing process. Research Objective: To determine the influence of family support and maternal readiness on the anxiety of pregnant women in the third trimester before giving birth at TPMB Telukjambe Barat, Karawang Regency. Research Method: Quantitative research, the quantitative research study in this research is observational using a cross-sectional or cross-sectional approach which measures the independent variable and the dependent variable at the same time. The research was conducted at TPMB Teluk West Jambe , Karawang Regency in September-November 2023 with a total of 63 respondents. The sampling technique uses total sampling technique. Research Results: the majority of respondents found out of the 63 respondents studied that the majority of respondents were of productive age, namely 20-35 years, 56 respondents (89%), and for maternal age <20 years and >35 years, there were 7 respondents (11%). Of the 63 respondents from third trimester pregnant women, the majority experienced moderate anxiety, namely 32 respondents (51%), 27 respondents (43%) had mild anxiety, while 4 respondents (6%) experienced severe anxiety. Conclusions and Suggestions: There is a significant relationship between the influence of family support and maternal readiness and the anxiety of pregnant women in the third trimester before delivery. It is hoped that midwives will provide evaluations for health workers to better understand the emotional conditions of pregnant women and provide appropriate SOP (Standard Operating Procedure) interventions, when they find out that there is a relationship between husband's assistance and the anxiety of pregnant women facing childbirth, especially those at TPMB Telukjambe Barat, Karawang Regency.